Biphasic Palladium‐Catalyzed Hydroesterification in a Polyol Phase: Selective Synthesis of Derived Monoesters. Issue 12 (3rd June 2015) - Pruvost, Romain; Boulanger, Jérôme; Léger, Bastien; Ponchel, Anne; Monflier, Eric; Ibert, Mathias; Mortreux, André; Sauthier, Mathieu
Abstract The palladium‐catalyzed hydroesterification reaction was performed with polyols and olefins in a liquid/liquid biphasic system composed of unreacted polyol on the one hand and apolar reaction products/organic solvents on the other hand. The palladium‐based catalyst was immobilized in the polyol phase thanks to the use of cationic triarylphosphines possessing pendent protonated amino groups in the acidic reaction medium or to the sulfonated phosphine TPPTS (trisodium triphenylphosphine‐3, 3′, 3′′‐trisulfonate). Owing to the insolubility of the products in the catalytic phase, this approach allowed the synthesis of monoesters of polyols with high selectivities as well as the easy separation of the catalyst through simple decantation.